Outcomes of coronary revascularization in patients with metabolic dysfunction-associated steatotic liver disease: a systematic review - Gries, Jacob J.; Hassan Virk, Hafeez Ul; Wang, Zhen; Alam, Mahboob; Sharma, Samin; Strauss, Markus; Krittanawong, Chayakrit (Frontiers in Cardiovascular Medicine, 2025)
IntroductionA growing amount of evidence suggests that metabolic dysfunction-associated steatotic liver disease (MASLD) may independently increase the risk of coronary artery disease and acute coronary syndrome, thus necessitating revascularization interventions such as percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) [2,3]. However, a limited number of studies have evaluated the impact of MASLD on the outcomes of these interventions.MethodsA comprehensive search of the PubMed/MEDLINE and Embase databases was conducted to identify relevant studies from August 2015 to August 2025 using a combination of Medical Subject Headings (MeSH) terms and text words related to MASLD and cardiovascular revascularization.ResultsTwo hundred nineteen papers from the PubMed/MEDLINE and Embase databases were reviewed. Six met the inclusion criteria ( Figure 1). Five studies covered PCI, and one covered CABG. Supplemental information was added using targeted PubMed/MEDLINE searches.ConclusionsMASLD may pose an increased risk of in-hospital and long-term mortality following PCI. Risks for cardiogenic shock, cardiac arrest, in-stent thrombosis, gastrointestinal bleeding, or invasive mechanical ventilation following PCI may also be increased. Further studies are needed to determine the optimal coronary revascularization method and post-revascularization medical therapy for patients with MASLD.